Pulmonary arteriovenous malformation unmasked in pregnancy: A case report. (December 2013) - Anin, Sheba Reshmi; Ogunnoiki, Wunmi; Sabharwal, Tarun; Harrison-Phipps, Karen
Pulmonary arteriovenous malformations are anomalous communications between arteries and veins of the pulmonary vasculature. Its incidence is rare. Pulmonary arteriovenous malformations can be asymptomatic or cause profound cardiovascular compromise and adverse neurological sequelae, as a result of right to left shunting of deoxygenated blood. Pregnancy and its physiological demands can unmask and exacerbate pulmonary arteriovenous malformations with attendant risks of life threatening complications and rarely, death. This case report describes a first presentation of pulmonary arteriovenous malformation in pregnancy and the tendency for misdiagnosis with pulmonary embolism. A multidisciplinary approach to management is pertinent considering the challenges involved in deciding the appropriate therapeutic management in pregnancy which has to be weighed against potential maternal and fetal risks.